Transition of youth and young adults - Cook, Bryan G.; Tankersley, Melody; Landrum, Timothy J. (Advances in learning and behavioral disabilities ;, 2015)
How do students with learning disabilities or emotional and behavioral disorders fare in adulthood? Are their rates of employment, graduation from post-secondary schools, living independently similar to their non-disabled peers? What can schools and communities do to teach and support youth and young adults with learning disabilities or emotional and behavioral disorders? This Transition of Youth and Young Adults volume presents eminent scholars discussing critical and timely topics related to the transition of youth and young adults with learning disabilities and emotional and behavioral disorders and provides a comprehensive selection of chapters that address variables, issues, practices, and outcomes related to the broad topic of transition.